2019
DOI: 10.3390/agronomy9100586
|View full text |Cite
|
Sign up to set email alerts
|

Seed Coating with Thyme Essential Oil or Paraburkholderia phytofirmans PsJN Strain: Conferring Septoria Leaf Blotch Resistance and Promotion of Yield and Grain Isotopic Composition in Wheat

Abstract: Septoria leaf blotch (SLB) is considered one of the most devastating diseases affecting global wheat production. Biostimulant application is among the modern approaches in plant protection to overcome the impact of SLB’s fungicide resistance. In this manner, the effect of coating seeds with thyme essential oil or Paraburkholderia phytofirmansPsJN strain on SLB severity and yield components (spikes/m2, straw yield (SY), grain yield (GY) and thousand kernel weight (TKW)) were assessed under field conditions for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
4
14
0
Order By: Relevance
“…Seed coating with beneficial microorganisms has been proposed as a very effective approach to promote durum wheat yield [ 8 ]. Previous studies demonstrated that treatment with M. guilliermondii improves maize ( Zea mays L.) productivity and reduces the needs for chemical fertilization [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Seed coating with beneficial microorganisms has been proposed as a very effective approach to promote durum wheat yield [ 8 ]. Previous studies demonstrated that treatment with M. guilliermondii improves maize ( Zea mays L.) productivity and reduces the needs for chemical fertilization [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In details, surface-sterilized seeds were soaked in the conidial suspension of F. culmorum or in sterile distilled water containing 0.05% Tween 20 as the non-infected control. The soaking seeds were kept for 16 h in the dark at 25 °C [ 8 ]. Afterwards, both infected and non-infected seeds were coated with M. guilliermondii filtrate as described by [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors concluded that soy flour provided a sustained source of key amino acids, thus positively influencing N uptake and transplant quality. Furthermore, Ben-Jabeur et al [24] conducted a three-year experiment on durum wheat aiming to assess the effect of coating wheat seeds with thyme essential oil or Paraburkholderia phytofirmans PsJN strain on yield and resistance/tolerance to spetoria leaf botch. The two tested biostimulants were able to alleviate the Septoria leaf botch and to enhance yield in terms of number of spikes per square meter as well as straw and grain yields.…”
Section: The Role Of Non-microbial and Microbial Biostimulants In Mormentioning
confidence: 99%